Pendampingan Dan Sosialisasi Ketahanan Keluarga Melalui Pendekatan Financial Resilience Di Desa Bulmatet Karang Penang - Fahmi Assulthoni (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2025)
Financial resilience within households is always a persistent issue that haunts every family. It is a latent problem that requires special attention to prevent it from spreading and disrupting family stability and unity. Not all families are able to face enormous economic pressures without being equipped with maturity and strength in managing and handling their finances. In Bulmatet village, the community, based on the author's findings, needs mentoring and socialization to maintain family unity from the perspective of financial resilience. They admitted that they have not yet fully understood that financial resilience is one of the factors that can affect family resilience. This article aims to gather information and provide some solutions that the local community can apply in their social lives. It is hoped that the community can preserve and strengthen the integrity of their households through financial strength and resilience. The mentoring activities were conducted using socialization methods, including location surveys, program socialization, lectures, and discussions to deliver the material, concluded with general conclusions and evaluations. Based on the results of the mentoring, it is concluded that the people of Bulmatet village were very enthusiastic in participating in the mentoring and socialization program. They realized that financial resilience is one of the key factors in maintaining family resilience. Furthermore, they hope similar activities will continue to be held with topics that address other social issues